Galactose Enhances Chondrogenic Differentiation of ATDC5 and Cartilage Matrix Formation by Chondrocytes - Yuan, Zhongrun; Liu, Sa; Song, Wenjing; Liu, Ying; Bi, Gangyuan; Xie, Renjian; Ren, Li (Frontiers in Molecular Biosciences, 2022)
Galactose, an important carbohydrate nutrient, is involved in several types of cellular metabolism, participating in physiological activities such as Glycosaminoglycan (GAG) synthesis, glycosylation and intercellular recognition. The regulatory effect of galactose on osteoarthritis has attracted increased attention. In this study, in vitro cell models of ATDC5 and chondrocytes were prepared and cultured with different concentrations of galactose to evaluate its capacity on chondrogenesis and cartilage matrix formation. Cell proliferation assay demonstrated that galactose was nontoxic to both ATDC5 cells and chondrocytes. RT-PCR and immunofluorescence staining indicated that the gene expression of cartilage matrix type II collagen and aggrecan were significantly up-regulated with increasing galactose concentration as well as the expression and accumulation of Extracellular Matrix (ECM) protein. Overall, these results indicated that a galactose concentration below 8 mM exhibited the best effect on promoting chondrogenesis, which entitles galactose as a considerable potential for cartilage repair and regeneration.